Nanozirconia polymer composite porous membrane prepared by sustainable immersion precipitation method for use as electrolyte in flexible supercapacitors. (December 2020) - Yadav, Nitish; Mishra, Kuldeep; Hashmi, S.A.
Graphical abstract: Highlights: PVdF-HFP - ZrO2 nanocomposite porous membranes are prepared by phase inversion. Nanofiller modifies microstructure, pore-morphology upon interaction with polymer. Surface groups on nanofiller modify charge-transfer in the electrolyte. Supercapacitors fabricated with nanofiller incorporated membrane perform better. Charge-discharge studies show better cyclic stability with ZrO2 nanofiller. Abstract: We report ZrO2 -polymer nanocomposite porous membranes prepared by one step phase inversion method with the aim to study a) the effect of ZrO2 nanofiller on the physiochemical and electrochemical properties of the membranes, and b) the viability of the optimized membrane as an electrolyte in energy storage devices. The interaction of ZrO2 nanoparticles with the polymer and liquid electrolyte has been investigated in details using scanning electron microscopy, x-ray diffraction, and Fourier transform infrared spectroscopy. The microporous structure, liquid electrolyte uptake and ionic conductivity of the nanocomposite membranes have been found to be affected by presence of ZrO2 nanoparticles. The electrolyte membrane with 3 wt.% ZrO2 shows the highest ionic conductivity of ∼4.4 mS cm −1 with a liquid electrolyte retention of ∼375 % and electrochemical stability of ∼4.25 V when soaked in a sodium-ion conducting organic electrolyte. The performance of the highest conducting nanocomposite membrane in symmetric electrical double-layer capacitor (EDLC) has been observed to be better as compared to that of un-doped electrolyte membranes. The EDLC fabricated using the optimized electrolyte membrane and activated carbon electrodes exhibits specific capacitance ∼103 F g −1 and is stable up to 50, 000 charge–discharge cycles with specific energy ∼10.2 Wh kg −1, specific power ∼14.2 kW kg −1, and Coulombic efficiency ∼ 99.8 %.